Environmental evaluation of cogeneration scenarios in sugar industry - Colombo, Mauricio; Mele, Fernando Daniel; Hernandez, Maria Rosa; Gatica, Jorge E.; Silveira Sr., José Luz [UNESP] (My University, 2008)
The development of new techniques that allow the analysis and optimization of energy systems bearing in mind environmental issues is indispensable in a world with finite natural resources and growing demand of energy. Among the energy systems that deserve special attention, cogeneration in the sugar industry must be pointed out, because it uses efficiently a common fuel for generation of useful heat and power. Within this frame, thermoeconomical optimization - 2nd Law of Thermodynamics analysis by exergy function and economic evaluation of the thermal system - gradually is taking importance as a powerful tool to assist to the decision making process. Also, the explicit consideration of environmental issues offers a better way to explore trade-offs between different aspects to support the decisions that must be made. In this work it is used the technique of Life Cycle Analysis (LCA) which allows to consider environmental matters as an integral part of the problem, in opposite to most of the environmental approaches that only reduce residuals generation , without taking into account impacts associated to other related processes. On the other hand, the consideration of environmental issues in optimization of energy systems is a novel and promissory contribution in the state of the art of energy optimization and LCA. The system under study is a sugar plant of Tucumán (Argentina) given the particular importance that this industry had inside the regional economy of the Argentinean Northwest. Although cogeneration comes being used a while ago in sugar industry, being the main objective the generation of heat and as secondary objective the electric power generation and mechanic power to cover several needs of working machineries, to the date it is no available a versatile tool that allows to analyze economical feasible alternatives bearing in mind environmental issues. At sugar plants, steam is generated in boilers using as fuel bagasse - cellulosic fiber waste obtained crushing the sugar cane- and it is used to give useful heat and shaft work to the plant, but it can also be used to generate electricity with export opportunities to the electrical network. The great number of process alternatives outlines a serious decision making problem in order to take advantage of the resources. Although the problem turns out to be a mixed non-linear problem (MINLP), the main contribution of this work is the development of a hybrid strategy to evaluate cogeneration alternatives that combines optimization approaches with environmental indicators. This powerful tool for its versatility and robustness to analyze cogeneration systems, will be of great help in the decision making process, because of their easy implementation to analyze the kind of problems presented in the sugar industry.
Keywords: Cogeneration; Environmental impact; Optimization; Sugar industry